PENGARUH TINGKAT EFISIENSI, SISTEM PENGHARGAAN DAN BUDAYA PERUSAHAAN TERHADAP KEPUASAN KERJA DAN DAMPAKNYA PADA KINERJA KARYAWAN (STUDI KASUS: BANK MUAMALAT CABANG LAMPUNG) - Denny Kurniawan (Derivatif : Jurnal Manajemen, 2018)
This research is meant to analyze the influence of efficiency, reward system and corporate culture toward work satisfaction and the impact to employees performance in Muamalat Bank of Lampung Branch. The sample for this research are 50 employees. The result of this research shows that: 1) efficiency have direct positif influence and significant toward work satisfaction, 2) reward have not significant influence toward work satisfaction, 3) corporate culture have direct positif influence and significant toward work satisfaction, 4) efficiency have direct positif influence and significant toward performance, 5) corporate culture have direct positif influence and significant toward performance, and 6) work satisfaction have not significant influence toward performance.   Keyword: Efficiency, reward, corporate culture, work satisfaction and performance